Teenage martial arts groups: trainer’s locus of control versus trainees self-control tests and analyses - Kirpikov, A.R.; Baranov, A.A.; N.Y. Erofeeva (Theory and Practice of Physical Culture, 2022)
Objective of the study was to rate and analyze effects of the trainer’s locus of control on the trainees’ behavioral self-control and personality progress. Methods and structure of the study. We sampled for the study two coaches with the polar (external and internal) locus of control, plus their teenage trainees having 2-3-year training and competitive experiences under their management (n=20). The trainees’ and trainers’ self-control were tested by the V.I. Morosanova Behavioral Self-control Style test (BSCS) and the locus of control in the interpersonal and business relations and personal problem solving was rated by the A.K. Osnitsky locus of control test. Conclusion. We found the trainer locus of control largely influential on the trainees’ one; whilst the BSCS of the young athletes are likely to be sport-specific and dictated by the individual motivations. It should be emphasized, however, that the trainees of trainer with the internal locus of control tend to mimic his attitudes in solving business problems; whilst the trainees of trainer with external locus of control tend to rely on external control in solving their business problems. A trainer’s locus of control was found to influence some aspects of the trainees’ self-control. Thus the group of trainer with internal locus of control was tested with better action programming qualities and more independent in the activity planning, behavioral control, goal attainment, progress rating, and interim/ final result rating domains. The group of trainers with external locus of control was tested with a better planning ability, individual goal setting and progress management skills.